Fulfilling the Process Promise: A Review and Agenda for New Venture Creation Process Research. (September 2021) - Davidsson, Per; Gruenhagen, Jan Henrik
We review new venture creation process research in leading journals over the past 30 years, applying a broad view of "process." While we find a rich and varied literature with significant quantitative and qualitative growth, the review reveals considerable room for future contributions in this important area of entrepreneurship research. In an agenda building on review results, exemplary articles, and theory development advice from other sources, we discuss several types of such future contributions. We hope that our efforts can inspire emerging scholars, colleagues, research leaders, and institutional actors to contribute to a bright future for this core domain of entrepreneurship research.